Bird Collection of Otto Hedin - Anders Telenius (GBIF Sweden, 2015)
This dataset contains information on 423 registered specimens of the private collection of birds by Otto Hedin currently curated at Kärrboda Gårdsmuseum, Nyköping, Sweden. The dataset was prepared by Kristina Hedin in 2014. The collection contains specimens collected between 1810 and 1915.
Keywords: Occurrence; Specimen; Occurrence; OCCURRENCE; Biological Sciences; Biologi